Bladder exstrophy closure using anterior pelvic osteotomy of superior pubic rami - Hassan, Moaied A. (Journal of the Faculty of Medicine Baghdad, 2015)
Background: Bladder exstrophy is a rare and complex urogenital malformation. The current surgical approach consists of early closure followed by other procedures later on aiming for continence. Primary closure usually requires some form of osteotomy to facilitate successful bladder and abdominal wall repair. For decades, bilateral posterior iliac osteotomy has been the most commonly used technique. A new osteotomy technique, consisting of anterior pelvic ostecotomy of the superior pubic ramus, seems to be a safe and quick alternative method to obtain tension-free approximation of the symphysis pubis Patients and methods: A prospective study between 2006 and 2013, were 10 (9 males and 1 female) newborns underwent surgery for bladder exstrophy closure in the pediatric surgery department, using anterior pelvic osteotomy of superior pubic rami to achieve tension-free approximation of the symphysis pubis and successful repair. Results: Successful closure was achieved in 90% of the patients operated upon. Only 1 patient had wound dehiscence and failure of the repair. The procedure was safe, quick with minimal blood loss and was performed by the pediatric surgeon without the need to an orthopedic surgeon. Conclusion: Anterior pelvic osteotomy of superior pubic rami in an effective alternative measure to obtain tension-free approximation of the symphysis pubis, and hence successful bladder exstrophy repair. It provides further advantages namely, ease and rapidity, minimal blood loss, and no requirement for an extra skin incision or patient’s repositioning.